Carbon Microsphere – Polystyrene Composite Electrode for Three‐Phase Boundary Oil Analysis: Quinizarin in Methyllaurate. Issue 4 (12th February 2015) - Ahn, Sunyhik D.; Kaluza, Dawid; Jönsson‐Niedziólka, Martin; Mitchels, John M.; Marken, Frank; Rees, Neil V.
Abstract Oil analysis for the case of quinizarin in methyllaurate is demonstrated with a disposable carbon microsphere – polystyrene composite electrode. Oxidation and reduction of quinizarin are observed as three‐phase boundary processes at the immiscible oil | water | carbon interface. Randomly packed glassy carbon microspheres (2–12 µm diameter) held together with a polystyrene binder (ca. 0.1 % by weight) are immobilized onto a pencil lead electrode and used for electrochemical oil analysis. Pore‐filling with oil is optimised for voltammetric detection and fluorescence spectroscopy is employed to support the mechanistic analysis based on voltammetry. Future applications for a wider range of oils and additives are proposed.